Identification of miRNAs that target Fcγ receptor-mediated phagocytosis during macrophage activation syndrome - Varsha, Kontham Kulangara; Yang, Xiaoming; Cannon, Alkeiver S.; Zhong, Yin; Nagarkatti, Mitzi; Nagarkatti, Prakash (Frontiers in Immunology, 2024)
Macrophage activation syndrome (MAS) is a life-threatening complication of systemic juvenile arthritis, accompanied by cytokine storm and hemophagocytosis. In addition, COVID-19–related hyperinflammation shares clinical features of MAS. Mechanisms that activate macrophages in MAS remain unclear. Here, we identify the role of miRNA in increased phagocytosis and interleukin-12 (IL-12) production by macrophages in a murine model of MAS. MAS significantly increased F4/80+ macrophages and phagocytosis in the mouse liver. Gene expression profile revealed the induction of Fcγ receptor–mediated phagocytosis (FGRP) and IL-12 production in the liver. Phagocytosis pathways such as High-affinity IgE receptor is known as Fc epsilon RI -signaling and pattern recognition receptors involved in the recognition of bacteria and viruses and phagosome formation were also significantly upregulated. In MAS, miR-136-5p and miR-501-3p targeted and caused increased expression of Fcgr3, Fcgr4, and Fcgr1 genes in FGRP pathway and consequent increase in phagocytosis by macrophages, whereas miR-129-1-3p and miR-150-3p targeted and induced Il-12. Transcriptome analysis of patients with MAS revealed the upregulation of FGRP and FCGR gene expression. A target analysis of gene expression data from a patient with MAS discovered that miR-136-5p targets FCGR2A and FCGR3A/3B, the human orthologs of mouse Fcgr3 and Fcgr4, and miR-501-3p targets FCGR1A, the human ortholog of mouse Fcgr1. Together, we demonstrate the novel role of miRNAs during MAS pathogenesis, thereby suggesting miRNA mimic–based therapy to control the hyperactivation of macrophages in patients with MAS as well as use overexpression of FCGR genes as a marker for MAS classification.